Contextualizing temporal arterial magnetic resonance angiography in the diagnosis of giant cell arteritis: a retrospective cohort study. (6th January 2021) - Junek, Mats; Hu, Angela; Garner, Stephanie; Rebello, Ryan; Legault, Kim; Beattie, Karen; Khalidi, Nader
Abstract: Objectives: Imaging modalities have become common in evaluating patients for a possible diagnosis of GCA. This study seeks to contextualize how temporal arterial magnetic resonance angiography (TA-MRA) can be used in facilitating the diagnosis of GCA. Methods: A retrospective cohort study was performed on patients who had been previously referred to a rheumatologist for evaluation of possible GCA in Hamilton, Ontario, Canada. Data including clinical features, inflammatory markers, imaging, and biopsy results were extracted. Multivariable logistic regression model to predict the diagnosis of GCA. Using these models, the utility of TA-MRA in series with or in parallel to clinical evaluation was demonstrated across the cohort as well as in subgroups defined by biopsy and imaging status. Results: In total 268 patients had complete data. Those diagnosed with biopsy- and/or imaging-positive GCA were more likely to demonstrate classic features including jaw claudication and vision loss. Clinical multivariable modelling allowed for fair discriminability [receiver operating characteristic (ROC) 0.759, 95% CI: 0.703, 0.815] for diagnosing GCA; there was excellent discriminability in facilitating the diagnosis of biopsy-positive GCA (ROC 0.949, 0.898–1.000). When used in those with a pre-test probability of 50% or higher, TA-MRA had a positive predictive value of 93.0%; in those with a pre-test probability of 25% or less TA-MRA had a negative predictive value of 89.5%. Conclusion: In those with high disease probability, TA-MRA can effectively rule in disease (and replace temporal artery biopsy). In those with low to medium probability, TA-MRA can help rule out the disease, but this continues to be a challenging diagnostic population.